Musical Pitch Perception and Categorization in Listeners with No Musical Training Experience: Insights from Mandarin-Speaking Non-Musicians - Jie Liang; Fen Zhang; Wenshu Liu; Zilong Li; Keke Yu; Yi Ding; Ruiming Wang (Behavioral Sciences)
Pitch is a fundamental element in music. While most previous studies on musical pitch have focused on musicians, our understanding of musical pitch perception in non-musicians is still limited. This study aimed to explore how Mandarin-speaking listeners who did not receive musical training perceive and categorize musical pitch. Two experiments were conducted in the study. In Experiment 1, participants were asked to discriminate musical tone pairs with different intervals. The results showed that the nearer apart the tones were, the more difficult it was to distinguish. Among adjacent note pairs at major 2nd pitch distance, the A4–B4 pair was perceived as the easiest to differentiate, while the C4–D4 pair was found to be the most difficult. In Experiment 2, participants completed a tone discrimination and identification task with the C4–D4 and A4–B4 musical tone continua as stimuli. The results revealed that the C4–D4 tone continuum elicited stronger categorical perception than the A4–B4 continuum, although the C4–D4 pair was previously found to be more difficult to distinguish in Experiment 1, suggesting a complex interaction between pitch perception and categorization processing. Together, these two experiments revealed the cognitive mechanism underlying musical pitch perception in ordinary populations and provided insights into future musical pitch training strategies.